Population Growth Dynamics of Nepal: Evidence from Different Population Censuses - Pokhrel, Baijayantimala; Baral, Chandrakant (The Geographic Base, 2023)
Demographics processes – birth, death and migration, determine the population size and the growth rate of any place. Changes in one of these components affect population growth and size. Higher population growth creates stress on natural resources while lower growth causes shortage of human resources for several development activities. Based on the population growth data from 1981 to 2021 published by Central Bureau of Statistics, and National Statistical Office of Nepal, this paper analyzes the patterns and trends of population growth by ecological regions and districts of Nepal. The findings show that a high population growth has observed before 2001 compared to the two successive censuses i.e. 1.35% in 2011 and 0.92% in 2021. A significant change has been observed in the number of districts with negative population growth in Hill and mountain regions. Before 2001, the Hill region had 1 to 2 % population growth in general and Tarai had above 2 % which has declined to 0 to 1 % and 1 to 2 % respectively in 2021. The low growth can have a number of, and far reaching consequences for development such as shortage of human resources in agricultural and other various development activities in the country. It is thus, Nepal needs to review its population policy along with its employment and development policy at large.